Earnings Instability and Tenure - Lorenzo Cappellari; Marco Leonardi (Center for Economic Studies and ifo Institute (CESifo), 2013)
We study the effect of tenure on earnings instability in Italy using two alternative estimation strategies. First we use a descriptive measure of earnings instability and fixed effects regressions. Second, we develop a formal model of earnings dynamics distinguishing permanent from transitory earnings, and exploit variation of tenure and instability over time and across birth cohorts in estimation. We use the two approaches also to evaluate earnings instability associated with temporary contracts (short-tenure contracts). Our results indicate that each year of tenure on the job reduces earnings instability on average by 11%. Workers on a temporary contract have an earnings instability up to 50% higher than workers on a permanent contract.
Keywords: J21; J31; 330; earnings instability; earnings dynamics; tenure; temporary contracts; minimum distance estimation